Heterogeneous propagation of spreading depolarizations in the lissencephalic and gyrencephalic brain - Santos, Edgar; Sánchez-Porras, Renán; Sakowitz, Oliver; Dreier, Jens P.; Dahlem, Markus A. (Journal of cerebral blood flow & metabolism, 2017)
In the recently published article, "Heterogeneous incidence and propagation of spreading depolarizations," it is shown, in vivo and in vitro, how KCl-induced spreading depolarizations in mouse and rat brains can be highly variable, and that they are not limited, as once thought, to a concentric, isotropic, or homogenous depolarization wave in space or in time. The reported results serve as a link between the different species, and this paper contributes to changing the way in which SD expansion is viewed in the lissencephalic brain. Here, we discuss their results with our previous observations made in the gyrencephalic swine brain, in computer simulations, and in the human brain.